ANALISIS GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI UNTUK MENINGKATKAN KINERJA KARYAWAN DALAM PERSPEKTIF EKONOMI ISLAM (STUDI KASUS TOSERBA YOGYA KOTA BANJAR) - Vina Erdiani; Pepe Iswanto (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2019)
This study aims (1) to determine the leadership style to improve employee performance in the perspective of Islamic economics in Toserba Yogya, Banjar City; (2) to know the organizational culture to improve employee performance in the perspective of Islamic economics at the Yogya Department Store, Banjar City; and (3) to determine the performance of employees at the Yogya department store, Banjar City in the perspective of Islamic economics. Data were collected through observation and interviews with store managers, employees and consumers of the Yogya Banjar Department Store. The results showed that the leadership styles at the Toserba Yogya Banjar include democratic leadership style, analytical leadership style (analytical), and assertive leadership style (assertive). In the view of Islam, economics or iqtishad comes from the word